POST-EXERCISE REHYDRATION WITH DIFFERENT BEVERAGES: PURE WATER, SPORTS DRINK, AND ROSELLE TEA - María de Lourdes Mayol Soto; Luis Fernando Aragón Vargas (Pensar en Movimiento)
The purpose of the present study was to assess the suitability of roselle tea (Hibiscus Sabdariffa L.) for post-exercise rehydration, compared with pure water and a sports drink. Roselle tea is a beverage widely consumed in Mexico and highly regarded because of its purported diuretic properties. Sixteen physically active male students from the University of Costa Rica, aged 17 to 23 years old, drank each one of the three treatments on different days, the same day of the week, in random order. They arrived in the laboratory euhydrated and, after a standardized breakfast and a brief rest, exercised intermittently on a stationary bicycle in a climate-controlled room (30-35°C and 85% RH) until reaching 2.3% body mass loss dehydration. After a 30-min rest at room temperature, they drank a volume equivalent to 150% of their body mass loss of the drink assigned to that day, within 45 minutes. At the end of rehydration (0 min) urine collection was performed and repeated every 30 min for a total of 3 hours. Each sample was measured for volume, color and density. Sample volumes were analyzed as percentage of ingested fluid. Data were analyzed with descriptive statistics and  two-way ANOVAs (repeated measures on both factors). While there were no statistically significant differences in total urine output (p = 0.084), an interaction was found between urine output, density, and color, with time (p < 0.001). Post-hoc analysis showed urine output to be higher initially with the sports drink, but it was significantly lower at time points  150 and 180 min. In addition, urine was significantly darker and denser at 0, 150, and 180 min with this drink, suggesting greater fluid conservation. From the results it is possible to conclude that roselle tea did not show a diuretic effect 3 hours after consumption, in exercise-dehydrated subjects. While it seems like rehydration is almost identical with the three drinks, urine composition and output dynamics is different with each beverage. In addition, there was a tendency for the sports drink to be retained better in the body toward the end of monitoring.